INVESTIGATION OF IFI16 GENE VARIANTS ASSOCIATED WITH IMMUNE RESPONSE IN THE VIETNAMESE POPULATION - Ngo Truong Giang; Vu Thi Le; Hoang Van Tong; Le Thi Kim Dung; Nguyen Thi Viet Ha; Do Thanh Tung (Tạp chí Y học Quân sự, 2026)
Objectives: To determine the allele frequencies, genotype distribution and haplotype profiles of several variants within the promoter region of the IFI16 gene in the Vietnamese population. Subjects and methods: A cross-sectional descriptive study was conducted on 132 peripheral blood samples collected from unrelated healthy Viet individuals at the Department of Biology and Medical Genetics, Military Medical University, between September 2025 and February 2026. Genomic DNA was extracted using the GeneJET™ kit; two target segments within the promoter region were amplified via Polymerase Chain Reaction (PCR) and analyzed using Sanger sequencing. Data processing and genetic analysis were performed using MEGA X, SPSS 20.0 and Arlequin 3.5 software. Results: Six Single Nucleotide Polymorphisms (SNPs) were successfully genotyped: -1735A/C, -982A/G, -760G/T, -746A/G, -491A/C, and -224T/G. The Minor Allele Frequencies (MAFs) were determined to be 0.3410 (C), 0.0038 (G), 0.0909 (T), 0.3485 (G), 0.1250 (C), and 0.4242 (G), respectively. Haplotype analysis revealed 11 distinct combinations, among which AGAAG (42.0%), CGGAT (28.4%) and AGAAT (14.8%) were predominant, collectively accounting for over 85% of the total haplotype pool. Notably, the minor allele frequencies at rs3754466 and rs3754464 in the Viet cohort were significantly higher than those reported in European, African and American populations, while closely resembling East Asian populations. Conclusions: This study establishes the first comprehensive genetic dataset regarding the IFI16 gene promoter region in the Viet population. The findings confirm distinct genetic divergence from Western cohorts and provide a baseline foundation for future case-control studies exploring genetic susceptibility to infectious and autoimmune disorders.